Democratizing the media - Coenie de Villiers (Communicare)
Democratic change In South Africa has left the country reeling wrth exhiliration, but also battling with the difficulties of transfonnation. The media are no exception. The .: role of the Independent Broad· casting Authority as regulatory body becomes critical as the electronic media and radio In particular struggle through the transitional pains of deregulation, privatization and liberalization. The author brieny sketches the departure points and background for the ISA action frame, and then posits an implied warning against these objectives by using, inter alia. arguments posed in qualitative research by. in particular, Splichal (1992) and Rothenbuhler (1996) as a springboard. Parallels between media demqcratization in CentralEastern Europe and South Africa are drawn, and the danger of an overriding commercial motive in radio broadcasting is outlined.